Forced convection heat transfer in micro heat sinks with square and circular configuration (2023)
This paper reports the results of three-dimensional numerical optimisation of microchannel heat exchanger with square and circular cooling channels. The objective of the optimisation is to maximise the global thermal conductance or minimise global thermal resistance. Response surface optimisation methodology (RSM) is used in the numerical optimisation. A high-density heat flux (2.5×106𝑊/𝑚2) is imposed at the bottom surface of the unit cell microchannel and numerical simulation carried out using ANSYS Fluent commercial software package. The elemental volume and axial length 𝑁=10 𝑚𝑚 of the microchannel were all fixed, while the width was free to morph. The cooling technique employs single-phase water which flows through the rectangular block microchannel heat sink to remove the heat at the bottom of the microchannels in a forced convection laminar flow regime. The velocity of the fluid pumped across the microchannel axial length is the range 400≤𝑅𝑒𝑤≤500. Finite volume method (FVM) is used to descretised the computational domain and computational fluid dynamic (CFD) code employed to solve a series of governing equations. The effect of channel hydraulic diameter and Reynolds number of water-flow on peak wall temperature and minimised temperature are investigated and reported. The numerical results show that the microchannel with square cooling channel has the highest maximised global thermal conductance than the micro heat sink with circular configuration. The result of the numerical study agrees with what is in the open literature.